Nutrition, physical exercise and cancer prophylaxis: a systematic review article (Research, Society and Development, 2022)
Cancer (CA) is identified as the second cause of premature death in almost 100 countries around the world, where it is estimated that there are 600,000 new cases/year. According to the data presented by INCA, nutritional and food inadequacy is classified as the second cause of CA that can be prevented, given that foods have the ability to interfere in stimulating development or protecting against tumors. Appropriate PA, diet and body weight help some types of these and are capable of significantly increasing the risk of the disease. This is a systematic literature review, where the main databases of journals used for active searches of articles were: Scielo, PubMed, ACS, Google Scholar. In view of this, a healthy meal is essential and it is advisable to consume macronutrients and micronutrients daily, which are crucial to improve the proper functioning of the body. Patients experience persistent, mental, physical and emotional changes that influence their QOL, relating to the feeling of well-being and comprising a multidimensional panorama. FA is an interposition that helps manage the side effects of diagnosis and treatment. Thus, the present research proves to be of great value, in which it verifies the benefits that PE training and the adoption of a healthy diet offer during the treatment of AC. Nutritional preservation also highlights a greater effect on the quality of life and well-being of cancer patients, helping with treatment results, prognostic evolution and increased survival.